The effect of temperature on natural corrosion inhibition of carbon steel by using pineapple peels (ananascomosus l.) extract in acid sollution - Nursyafiqah, Jalaludin (2015)
Corrosion inhibitor is one of the suitable methods to control metals from corrosion. Pineapple is chosen as a corrosion inhibitor for this research because pineapple is one of the abundant resource in Malaysia and reported that pineapple peels have potential to be extract due to large amount of waste after processing. This corrosion inhibitor is biodegradable and do not harm environment which is not contain any toxic chemical. The purpose of this research is to study the inhibition efficiency of the pineapple peels from carbon steel coupon by considering effect of temperature, molarity of the acid and concentration of the inhibitor. The coupon was leaved for one week in acidic solution for 7 days and weight loss method is used to calculate the efficiency of inhibitor and corrosion rate in each parameters. From the results, it shows that corrosion rate decrease when inhibitor concentration and temperature increase while molarity of acid decrease. From this research, the highest value of inhibition efficiency which is 80.34% is obtained at 0.0340g/mL of inhibitor concentration. Hence, inhibitor concentration plays and important role to prevent metal from rusting and give more effect towards the metal besides other parameters. The corrosion inhibition action is afforded by the adsorption of the components of the inhibitor onto the carbon steel surface. Therefore, it is shows that the adsorption of the compound in the pineapple peels towards the coupon is responsible for corrosion inhibition effect.